2001
DOI: 10.1161/01.cir.103.5.630
|View full text |Cite
|
Sign up to set email alerts
|

Increased Angiotensin-Converting Enzyme Activity in Coronary Artery Specimens From Patients With Acute Coronary Syndrome

Abstract: The present study demonstrates increased ACE activity in culprit lesions in acute coronary syndrome, indicating that enhanced ACE activity is related to the causative mechanism of active coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 13 publications
4
31
0
1
Order By: Relevance
“…Although there is a general consensus that inhibition of endothelial ACE is important for the benefits of any ACEi, inhibition of adventitial ACE may be just as important especially in clinical management of hypertension, heart failure, and/or ischemic heart disease or coronary atherosclerosis, because these disorders are associated with vascular hypertrophy, left ventricular remodeling, and atherosclerotic plaque formation. A recent report indicated that coronary artery ACE activity was approximately 5-fold higher in patients with acute coronary syndrome even though serum ACE activity was not different, 6 suggesting that inhibition of vascular and/or cardiac ACE is very important for the clinical benefits of ACEi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a general consensus that inhibition of endothelial ACE is important for the benefits of any ACEi, inhibition of adventitial ACE may be just as important especially in clinical management of hypertension, heart failure, and/or ischemic heart disease or coronary atherosclerosis, because these disorders are associated with vascular hypertrophy, left ventricular remodeling, and atherosclerotic plaque formation. A recent report indicated that coronary artery ACE activity was approximately 5-fold higher in patients with acute coronary syndrome even though serum ACE activity was not different, 6 suggesting that inhibition of vascular and/or cardiac ACE is very important for the clinical benefits of ACEi.…”
Section: Discussionmentioning
confidence: 99%
“…A deletion polymorphism in the ACE gene (DD) has been linked to increased circulating and tissue levels of ACE, 5 and indeed ACE activity is markedly increased in coronary arteries of patients with acute coronary syndrome. 6 High levels of circulating and tissue ACE may lead to increased tissue Ang II formation in the vascular wall, which induces vascular injury and subsequent hypertrophy and stenosis. Beneficial effects of ACEi may also be associated with increased bioavailability of nitric oxide (NO) in high-risk patients with ischemic heart disease.…”
mentioning
confidence: 99%
“…Interestingly, ACE activity was significantly increased in the culprit coronary lesions of patients with acute coronary syndrome compared with patients with stable ischemic heart disease. 96 Intervention studies in atherosclerotic animal models have shown the atherogenic effect of Ang II and the antiatherogenic effect of ACE inhibitors. Continuous administration of Ang II to ApoE Ϫ/Ϫ mice significantly increased lesion size.…”
Section: Ace and Atherosclerosismentioning
confidence: 99%
“…This is akin to the phenomenon of upregulation of receptors when they are exposed constantly to an antagonist drug. The second possibility is that progressive atherosclerosis in the vasculature induces ACE activity [14][15][16]. However, overt atherosclerosis is not prominent in brachial arteries, although there may be enough progressive vascular/endothelial dysfunction to induce local ACE activity.…”
Section: Discussionmentioning
confidence: 99%